Intellectual-creative methodological environment as a factor in the development of professional competences of vet teachers - Hryzhenko, V. (Problems of Engineer-Pedagogical Education, 2020)
The article defines the need to create an intellectual-creative methodological environment as a factor in the development of professional competences of VET teachers. The concepts of "educational space" and "educational environment" are analyzed. The intellectual-creative methodological environment is defined as a kind of educational environment. It is established that the intellectual-creative methodological environment should be multivariate, thus ensuring free development and, consequently, the implementation of a truly humanistic educational process. The intellectual-creative methodological environment is characterized by the innovative orientation of the formation of VET teachers' professional knowledge, knowhow and skills, and ensures their involvement in creative activity aimed at designing, assimilating and using pedagogical innovations in their teaching experience. The essence of pedagogical creativity is defined as a holistic process of teachers’ professional and self-realization in the intellectual-creative methodological environment. Teachers’ aptitude for creative work in education is characterized by a high level of creativity. The research proves that the intellectual-creative methodological environment undoubtedly affects the intellectual and creative potential of the teacher. Establishing an intellectual-creative methodological environment in vocational education institutions contributes to the actualization of the value-meaningful development of the teacher's personality, creates preconditions for professional growth, which involves boosting teachers’ ability to understand, formulate and solve professional problems and solve the problems of their professional selfdevelopment. The main indicators of the effectiveness of the intellectual-creative methodological environment of vocational education institutions are strategic orientation, full coverage, intensity, dominance, orderliness, consistency, and mobility. The object of further research on this issue is the form and methods of the development of professional competences of VET teachers in the context of the intellectual-creative methodological environment in the institution of vocational technical education.